Food-washing monkeys recognize the law of diminishing returns - Jessica E Rosien; Luke D Fannin; Justin D Yeakel; Suchinda Malaivijitnond; Nathaniel J Dominy; Amanda Tan (eLife)
Few animals have the cognitive faculties or prehensile abilities needed to eliminate tooth-damaging grit from food surfaces. Some populations of monkeys wash sand from foods when standing water is readily accessible, but this propensity varies within groups for reasons unknown. Spontaneous food-washing emerged recently in a group of long-tailed macaques (Macaca fascicularis) inhabiting Koram Island, Thailand, and it motivated us to explore the factors that drive individual variability. We measured the mineral and physical properties of contaminant sands and conducted a field experiment, eliciting 1282 food-handling bouts by 42 monkeys. Our results verify two long-standing presumptions: monkeys have a strong aversion to sand and removing it is intentional. Reinforcing this result, we found that monkeys clean foods beyond the point of diminishing returns, a suboptimal behavior that varied with social rank. Dominant monkeys abstained from washing, a choice consistent with the impulses of dominant monkeys elsewhere: to prioritize rapid food intake and greater reproductive fitness over the long-term benefits of prolonging tooth function.